Fundamental Understanding Of Hingeless Hub Proprotor Stability - O'Brien, N.; Delgado, X.; Akinwale, A.; Datta, A. (My University, 2024)
A 4.75-ft diameter hingeless hub tiltrotor model was developed and tested for aeroelastic stability up to a high speed of 200 knots corresponding to 468 knots full-scale. The model had interchangeable hubs, blades, and pylon center of gravity, allowing data acquisition for various new parametric variations. This paper documents the model, data and the insights gained from the test. The key conclusion is that a hingeless hub, when equipped with swept-tip blades, may significantly increase the stability compared to the state-of-the-art gimballed hub with straight blades. The causes were dissected using an in-house rotor comprehensive analysis to be the interaction of rotor regressive lag with wing-pylon modes, and the hub pitch and roll moments. The regressive lag was more important at lower speeds whereas the hub moments were more important at higher speeds. The torsion data was generally hard to measure and also hard to predict. Overall, the new data set shed light on high-speed tiltrotor flight and provided an unique database for validation of advanced rotor comprehensive analysis.